Household food security and HIV status in rural and urban communities in the Free State province, South Africa - Michélle Pienaar; Francois C. van Rooyen; Corinna M. Walsh (Taylor & Francis Group, 2017)
Higher socioeconomic status impacts profoundly on quality of life. Life-event stressors, such as loss of employment, marital separation/divorce, death of a spouse and food insecurity, have been found to accelerate disease progression among people with human immunodeficiency virus (HIV). The objective of this study was to determine significant independent sociodemographic and food security factors associated with HIV status in people from rural and urban communities in the Assuring Health for All study, which was undertaken in rural Trompsburg, Philippolis and Springfontein and urban Mangaung, in the Free State Province of South Africa. Sociodemographic and food security factors associated with HIV status were determined in 886 households. Logistic regression with forward selection (p < 0.05) was used to select significant independent factors associated with HIV status. Variables with a p-value of <0.15 were considered for inclusion in the model. Adults 25-64 years of age were eligible to participate. Of the 567 rural participants, 97 (17.1%) were HIV-infected, and 172 (40.6%) of the 424 urban participants. A relatively high percentage of respondents had never attended school, while very few participants in all areas had a tertiary education. The unemployment rate of HIV-infected adults was higher than that of HIV-uninfected adults. A high percentage of respondents in all areas reported running out of money to buy food, with this tendency occurring significantly more among urban HIV-infected than HIV-uninfected respondents. In all areas, a high percentage of HIV-infected respondents relied on a limited number of foods to feed their children, with significantly more HIV-infected urban respondents compared to their uninfected counterparts reporting this. Most participants in all areas had to cut the size of meals, or ate less because there was not enough food in the house or not enough money to buy food. During periods of food shortage, more than 50% of respondents in all areas asked family, relatives or neighbours for assistance with money and/or food, which occurred at a higher percentage of HIV-infected rural participants compared to HIV-uninfected rural participants. More than half of all participants reported feeling sad, blue or depressed for two weeks or more in a row. HIV infection was negatively associated with being married (odds ratio 0.20 in rural areas and 0.54 in urban areas), while church membership decreased the likelihood of HIV (odds ratio 0.22 in rural areas and 0.46 in urban areas). Indicators of higher socioeconomic status (having a microwave oven and access to vegetables from local farmers or shops) decreased the likelihood of HIV in rural areas (odds ratios 0.15 and 0.43, respectively). Indicators of lower socioeconomic status such as spending less money on food in the rural sample (odds ratio 3.29) and experiencing periods of food shortages in the urban sample (odds ratio 2.14), increased the likelihood of being HIV-infected. Interventions aimed at poverty alleviation and strengthening values can contribute to addressing HIV infection in South Africa.